Application of artificial intelligence technology in typhoon monitoring and forecasting - Zhou, Guanbo; Fang, Xiang; Qian, Qifeng; Lv, Xinyan; Cao, Jie; Jiang, Yuan (Frontiers in Earth Science, 2022)
In recent years, with the emergence of new artificial intelligence (AI) technology and more observational data from automatic meteorological stations, radars and satellites, the deep learning has very broad application scenarios in the context of meteorological big data. The deep learning has powerful data learning ability and feature capturing ability of complex structures, which has now occupied an important position in the meteorological field and also become a hot topic in meteorological research. Especially, AI has shown great potential advantages in image recognition, which can provide new ideas and new directions for typhoon monitoring and forecasting. In this study, based on the best track data set of typhoons by the China Meteorological Administration from 2005 to 2020, the Himawari-8 and FY4 satellite image data, we use the deep learning model in typhoon vortex identification, determining typhoon location and intensity, and detecting typhoon intensity mutation by introducing favorable factors in the large-scale environmental background field with AI techniques. The main research content includes a typhoon vortex identification model based on deep image target detection, an intelligent typhoon intensity determination model based on image classification and retrieval, and a typhoon rapid intensification identification model. Then, a typhoon intelligent monitoring and forecasting system is constructed. The results show that the system can correctly identify typhoon vortices above the strong tropical storm grade in a percentage of 88.6%. The mean absolute error (MAE) and Root mean square deviation (RMSE) of typhoon intensity estimation are 3.8 m/s and 5.05 m/s, respectively, and the comprehensive accuracy of rapid intensification estimation of annual independent samples reaches 92.0%. The system is capable of performing the automatic identification, location and intensity determination, and intelligent tracking of tropical cyclones in real time by using high spatial and temporal resolution satellite images. This study may help further improve the operational techniques for monitoring and forecasting typhoons in China.